Oral Histories of Older Gay Men in Hong Kong : Unspoken but Unforgotten - Kong, Travis S. K. (Book collections on Project MUSE., 2019)
""This is very personal and private, but I've told you everything."" Old Chan thus gives voice to the attitude expressed in all thirteen stories told in this intimate oral history of life at the margins of Hong Kong society, stories punctuated by laughter, joy, happiness, and pride, as well as tears, anger, remorse, shame, and guilt. Illustrated with photos, letters, and other images, Oral Histories of Older Gay Men in Hong Kong: Unspoken but Unforgotten gives voice to the complexities of a ""secretive"" past with unique hardships as these men came to terms with their sexuality, adulthood, and.